2011
DOI: 10.3233/bmr-2011-0277
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pulsed radiofrequency treatment on the saphenous nerve in patients with chronic knee pain

Abstract: PRF application to the saphenous nerve for eight minutes showed remarkable amount of patient satisfaction. Application of PRF for the second time could be recommended if it shows some benefit after the sixth month. But none of our patients needed a second application of PRF after six months period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 0 publications
4
53
0
5
Order By: Relevance
“…[18][19][20][21][22][23][24][25] The increasing number of publications concerning knee joint RFA is reflecting the growing clinical interest in this method. In a recent review of knee RFA denervation, Bhatia et al 26 concluded that the anatomical basis for radiofrequency cannula placement was often unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25] The increasing number of publications concerning knee joint RFA is reflecting the growing clinical interest in this method. In a recent review of knee RFA denervation, Bhatia et al 26 concluded that the anatomical basis for radiofrequency cannula placement was often unclear.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Even though the previous cadaveric studies have identified numerous sources of knee joint innervation including the genicular, common fibular (peroneal), and femoral nerves, [8][9][10][11][12][13][14][15][16][17] the majority of clinical RFA studies were focused on the genicular and/or saphenous nerves. [18][19][20][21][22][23][24] Optimizing the effectiveness of knee denervation relies on the precise localization of the articular branches innervating the joint capsule. Therefore, the objectives of this cadaveric study were to (1) elucidate the innervation of the anterior knee joint; (2) identify bony and soft tissue landmarks related to the articular branches discernable by ultrasound and/or fluoroscopy; (3) trace the nerves and estimate how frequently each articular branch is present; (4) document the distance of each articular branch from the bone surface; and (5) define the articular branches innervating the superolateral, inferolateral, superomedial, and inferomedial quadrants of the knee joint.…”
mentioning
confidence: 99%
“…28,29 Thirteen publications including 329 patients were included for reporting and discussion in this narrative review. [16][17][18][19][20][21][30][31][32][33][34][35][36] Eight of these publications were from the last 2 years.…”
Section: Search Resultsmentioning
confidence: 99%
“…Fluoroscopy has been used as an adjunct to pulsed radiofrequency [ 44 ] and cryoneuroablation of the IPS (see section " Cryoneuroablation " below), but has very little role in diagnostic injections.…”
Section: Fluoroscopy-guided Injectionsmentioning
confidence: 99%
“…Akbas et al [ 44 ] described the use of pulsed radiofrequency (PRF) lesioning of the IPS for treatment of the pain of osteoarthritis of the knee. All of the 115 treated patients were "substantially improved" by this therapy.…”
Section: Radiofrequencymentioning
confidence: 99%